Inducing labour in the United Kingdom: A feminist critical discourse analysis of policy and guidance - Cassandra Yuill; Mairi Harkness; Chlorice Wallace; Christine McCourt; Helen Cheyne; Lia Litosseliti (Elsevier, 2022)
Induction of labour (IOL), the process of starting labour artificially, is one of the most commonly performed procedures in maternity care in the United Kingdom (UK), yet there is debate whether inducing labour at 'term', in the absence of specific medical indication, is beneficial and reduces risk of stillbirth. Moreover, rates of routine IOL are rapidly rising in the UK, despite uncertainty about the evidence base and parents reporting receiving a lack of balanced information about the process. As a contested area of maternity care, the language used to debate, describe and discuss IOL takes on added significance and requires in-depth examination and analysis. To address this, we conducted a feminist critical discourse analysis on policy and professional writing about IOL in the UK, focusing on how these both reflect and construct social practices of pregnancy and birth. Our analysis identified a double discourse about IOL, which we term 'explicit-implicit discourse of care', revealing the differences between what is expected to be said and what is really said. Though most texts displayed an explicit discourse of care, which espoused women-centred care and informed choice, they also conveyed an implicit discourse of care, primarily composed of three key dimensions: women as absent actors, disembodiment, and evidence as a primary actor. We argue that this explicit-implicit discourse functions to preserve healthcare professionals' control over maternity care and further alienate women from their own bodies while maintaining a discursive position of women-centred care and informed choice.